2021
DOI: 10.1016/j.celrep.2021.109848
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Zn2+ release triggers rapid, mitochondria-mediated, non-apoptotic cell death in metastatic melanoma

Abstract: SUMMARY During tumor progression, lysosome function is often maladaptively upregulated to match the high energy demand required for cancer cell hyper-proliferation and invasion. Here, we report that mucolipin TRP channel 1 (TRPML1), a lysosomal Ca 2+ and Zn 2+ release channel that regulates multiple aspects of lysosome function, is dramatically upregulated in metastatic melanoma cells compared with normal cells. TRPML-specific synthetic agonists (ML-SAs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 63 publications
0
37
1
Order By: Relevance
“…In fact, our data are supported by a recently published study by Peng et al, who show that the lysosomal TRPML1 channel contributes to regulation of mitochondrial Ca 2+ dynamics at lysosome–mitochondria contact sites ( Peng et al, 2020 ). It is also worth mentioning, that TRPML1 is permeable for several cations, including Zn 2+ , which has been reported to induce cell death in melanoma cells upon pharmacological TRPML1 activation ( Du et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, our data are supported by a recently published study by Peng et al, who show that the lysosomal TRPML1 channel contributes to regulation of mitochondrial Ca 2+ dynamics at lysosome–mitochondria contact sites ( Peng et al, 2020 ). It is also worth mentioning, that TRPML1 is permeable for several cations, including Zn 2+ , which has been reported to induce cell death in melanoma cells upon pharmacological TRPML1 activation ( Du et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…While Otto Warburg postulated over 60 years ago, that mitochondria in cancer cells are ‘broken’ ( Warburg, 1956 ), they are now widely known to be essential in cancer cells, regulating, for example, metabolic reprograming, Ca 2+ homeostasis, generation of reactive oxygen species (ROS) and apoptotic cell death ( Lopez and Tait, 2015 ; Wallace, 2012 ). Interestingly, TRPML1 malfunction has been connected to defective Ca 2+ uptake of mitochondria ( Peng et al, 2020 ), while release of lysosomal Zn 2+ by TRPML1 caused mitochondria-mediated cell death ( Du et al, 2021 ). Hence, TRPML1 seems to have a balancing role in mitochondrial function and which we further investigated in hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…TRPML1 (transient receptor potential mucolipin 1, or ML1), a protein that is mutated in type IV mucolipidosis (MLIV, a neurodegenerative lysosome storage disease), is a Ca 2+ and Zn 2+ permeable cation channel predominantly localized on the late endosome and lysosome membrane, and is central to lysosome functions, such as lysosome trafficking and biogenesis, and lysosomal ion homeostasis. For the first time, we reported that ML-SAs (ML-specific synthetic agonists) induced ML1 activation and subsequent lysosomal Zn 2+ release via ML1, which causes a lysosomal Zn 2+ release triggered, mitochondria-mediated non-apoptotic cell death in metastatic melanoma cells ( Du et al., 2021 ).…”
Section: Before You Beginmentioning
confidence: 99%
“…Here, we present a protocol using GZnP3, a genetically encoded fluorescent Zn 2+ indicator, to assess lysosomal Zn 2+ release in cultured cells by fluorescence microscopy imaging. For complete details on the use and execution of this protocol, please refer to Du et al. (2021) or Minckley et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation